Can Millet Consumption Help Manage Hyperlipidemia and Obesity?: A Systematic Review and Meta-Analysis - Anitha, Seetha; Botha, Rosemary; Kane-Potaka, Joanna; Givens, D. Ian; Rajendran, Ananthan; Tsusaka, Takuji W.; Bhandari, Raj Kumar (Frontiers in Nutrition, 2021)
Many health benefits of millets (defined broadly to also include sorghum) have been are advocated, including their roles in positive impact on managing and preventing diabetes; however, the effects of millets on hyperlipidaemia (high lipid levels) have been understudiedis not well known. A systematic review and meta-analysis wereas conducted to collate the available evidences ofn the impacts of consuming millets consumption on lipid profilehuman body fats, namelyincluding total cholesterol (TC), triacylglycerol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and very-low-density lipoprotein cholesterol (VLDL- C). The results from 196 efficacy studies showed that the consumption of millets for periods as short as 21 days to about four months, has beneficial effects on reduceding levels of TC, triacylglycerol, LDL-C, and VLDL-C (p<0.01) by 7.8%, 9.411%, 9.710.4% and 9.08% respectively. Four Two studies demonstrated that consuming millets consumption can broughting TC and triacylglycerol levels to the normal levels (< 200 mg/dl and < 150mg/dl, respectively). FurthermoreOn the other hand, upon consumption of millet based meals, there was a slight increase of 6.05% increase in the HDL-C after consuming millet-based meals, a 4.0% and 5.0% reduction in systolic and diastolic blood pressure, and a 87.0% reduction in Body Mass Index (BMI). Based on Tthis evidence, leads us towe conclude that consumptionconsuming of millets is capablecan of reducinge hyperlipidaemia and hence hypertension, and raisingincrease levels of HDL-C (good cholesterolfats), which canmay be beneficial for managingreducing the associated risk of developing hypertension and atherosclerotic cardiovascular diseases in future.